2022
DOI: 10.1039/d1re00569c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of carbon-containing impurity methyldichlorosilane to purify raw material trichlorosilane of polysilicon production

Abstract: In order to remove the main carbon impurity methyldichlorosilane from the raw material trichlorosilane used in the production of polysilicon, the catalytic reaction was used to convert it into methyltrichlorosilane...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Typical chlorine sources for the chlorination reactions of CH 3 SiHCl 2 are chlorine gas, 8 chlorinated hydrocarbons 6,9 and chlorosilane. 4,10,11 Wan et al 8 proposed photochlorination of CH 3 SiHCl 2 with Cl 2 in a continuous microchannel reactor. The results showed that the removal rate of CH 3 SiHCl 2 was as high as 99.67% under the optimal reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical chlorine sources for the chlorination reactions of CH 3 SiHCl 2 are chlorine gas, 8 chlorinated hydrocarbons 6,9 and chlorosilane. 4,10,11 Wan et al 8 proposed photochlorination of CH 3 SiHCl 2 with Cl 2 in a continuous microchannel reactor. The results showed that the removal rate of CH 3 SiHCl 2 was as high as 99.67% under the optimal reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, silicon tetrachloride, a byproduct of polysilicon production via a modified Siemens process, can also be used as a chlorine source for chlorination of CH 3 SiHCl 2 . 4 However, silicon powder is easily formed, blocking the pores of the activated carbon catalyst during this process. Therefore, the catalytic performance and stability of the activated carbon catalyst are poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation